The expressions and behavior of solutions for nonlinear systems of rational difference equations - Alharbi, Kholoud N.; Elsayed, E. M. (Journal of Innovative Applied Mathematics and Computational Sciences, 2022)
In this paper, we investigate the form of the solutions of two systems of rational difference equations of second order, where the initial conditions are arbitrary nonzero real numbers.